IMPLEMENTATION OF GAME-BASED LEARNING MEDIA USING WORDWALL APPLICATIONS IN INCREASING STUDENTS' LEARNING MOTIVATION IN ISLAMIC RELIGIOUS EDUCATION SUBJECT - Syahrani. P, Shancy; Kustati, Martin; Amelia, Rezki; Gusmirawati, Gusmirawati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to find out about how the application of game-based learning media using wordwall applications in increasing students' learning motivation. This research is motivated by the lack of motivation from students in the learning process. The method used in this research is qualitative with a case study approach to see the phenomenon directly. The informants in this research were 21 informants, namely 1 PAI teacher and 20 fifth grade students at SDN 21 Lubuk Alung. Data collection using observation, interviews and documentation. In increasing the learning motivation of students using wordwall learning media as a medium for educational games such as quizzes, matchmaking, pairing, anagrams, word search word randomization and grouping. Based on the results of the research that has been done, wordwall learning media is proven to be able to increase the motivation and activeness of fifth grade students when learning Islamic Religious Education and this wordwall application has a very attractive appearance and makes it easier for teachers to convey material and foster students' interest and motivation to learn in Islamic Religious Education subjects. From this research it can be concluded that creative learning can produce good results, and seeing the main phenomenon of education today is bored and bored students in the learning process, therefore it can be overcome by the process of learning.